Analisis Kemampuan Pemecahan Masalah Matematis Siswa Berdasarkan Prosedur Polya ditinjau dari Self-efficacy pada Materi SPLTV - Irna Alawiyah; Hanifah Hanifah; Lessa Roesdiana (FKIP Universitas Mataram, 2026)
Mathematical problem-solving ability is not only related to the mastery of concepts and procedures but is also influenced by affective factors such as self-efficacy. This study aims to analyze students’ mathematical problem-solving abilities in the topic of Three-Variable Linear Equation System based on Polya’s procedures in terms of self-efficacy. This type of research is descriptive research with a qualitative approach. The study was conducted at a public senior high school in Bogor Regency involving 30 eleventh-grade students, with three students selected as the main subjects based on high, moderate, and low self-efficacy categories. Data were collected through a self-efficacy questionnaire and a mathematical problem-solving ability test based on Polya’s four-step procedures. The findings revealed that students with high self-efficacy were able to carry out all problem-solving procedures systematically and consistently. Students with moderate self-efficacy demonstrated fairly good ability but were not yet consistent, particularly lacking thoroughness in understanding the problem and still making errors at the evaluation stage. Meanwhile, students with low self-efficacy tended to experience difficulties in solving problems, characterized by a lack of problem understanding, inaccuracies in constructing mathematical models, and failure to evaluate the final results. These findings confirm that the higher a student’s self-efficacy, the better their problem-solving ability.